(untitled) (Journal of history, 2024)
The article delves into the historical research of cult-memorial sites from the Golden Horde era in the Saryarka region. It examines various perspectives regarding the emergence of sites influenced by the early spread of Islam in the central regions. The pre-revolutionary period is characterized by the fixation and description of the brightest and largest remains belonging to medieval mazars, mausoleums as well as buildings covered with glazed tiles. The descriptions were written by travelers, topographers, and prospectors in search for natural resources in the region. The second phase in the research timeline spans roughly from the latter half of the 20th century (from the mid-1940s to the 1980s). A.Kh. Margulan carried out the fixation and description of the memorial structures located on the caravan routes of Saryarka. He discovered the largest number of mausoleums in the valleys of the Sarysu, Kengir, Nura, Ishim, Turgai rivers, as well as in the oases of Betpakdala. The architectural monuments are located at a distance of 5 to 20 km from each other and indicate the presence of remnants of medieval settlements and towns along the Sarysui tract. A new stage in the study of Saryarka memorial monuments covers the 1990s of the twentieth century and the first decade of this century. It is associated with surveys, discoveries, and archaeological studies of mausoleums dated to the Golden Horde period. Over the past two decades, the archaeological expeditions of the K.A. Akishev Institute of Archaeology (Astana), A.Kh. Margulan Institute of Archeology (Almaty), the Margulan Center (Pavlodar), the Saryarka Archaeological Institute (Karaganda) have been repeatedly organized.